Computer aided design of active endoglucanase I from Fusarium oxysporum - Nor Azlina binti Mohd Said (Kuliyyah of Engineering, International Islamic University Malaysia, 2015)
The basic mechanism by which enzymes catalyze chemical reactions begins with the binding of the substrate (or substrates) to the active site on the enzyme. The active site is the specific region of the enzyme which combines with the substrate. The binding of the substrate to the enzyme causes changes in the distribution of electrons in the chemical bonds of the substrate and ultimately causes the reactions that lead to the formation of products. The new design of active endoglucanase I from Fusarium oxysporum were studied with the computational methods, hence the molecular docking has been done by using Autodock Vina based on Genetic Algorithm parameters with the cellotetraose as a ligand, while the energy minimization has done by using GROMOS96 implementation of Swiss-Pdb Viewer. E197R mutation from endoglucanase I with cellotetraose gave the lowest binding affinity which was -8.9 kcal/ mol after an energy minimization at 50000 steps of Steepest Descent. Furthermore, transition-state geometries were optimized by using Gaussian09 (integrated with QM/MM method) variation of ONIOM (n-layered integrated molecular orbital method) with a combination of Hartree Fock and UFF levels of theory. Hartree Fock has been selected as the High Layer while UFF as the Low Layer, by using TS (Berny), further compared with QST2 and QST3 calculations method.